2011
DOI: 10.1111/j.1365-2958.2011.07558.x
|View full text |Cite
|
Sign up to set email alerts
|

CaMtw1, a member of the evolutionarily conserved Mis12 kinetochore protein family, is required for efficient inner kinetochore assembly in the pathogenic yeast Candida albicans

Abstract: Summary Proper assembly of the kinetochore, a multi-protein complex that mediates attachment of centromere DNA to spindle microtubules on each chromosome, is required for faithful chromosome segregation. Each previously characterized member of the Mis12/Mtw1 protein family is part of an essential sub-complex in the kinetochore. In this work, we identify and characterize CaMTW1, which encodes the homolog of the human Mis12 protein in the pathogenic budding yeast Candida albicans. Subcellular localization and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
43
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 62 publications
(151 reference statements)
9
43
1
Order By: Relevance
“…However, results from immunofluorescence and ChIP assays in the present study unequivocally prove that the KT recruitment of the Dam1 complex is not dependent upon spindle MTs in C. albicans. This suggests that there are functional differences in the Dam1 complex of S. cerevisiae and C. albicans in terms of We observed that spindle defects associated with Spc19 and Dad2 are similar to those of inner (Cse4/CENP-A and Mif2/ CENP-C; present study) and middle (Mis12/Mtw1 [42]) KT proteins in C. albicans. Mtw1, a protein that is present in the linker layer of the kinetochore, showed similar spindle defects in C. albicans (42).…”
supporting
confidence: 50%
See 2 more Smart Citations
“…However, results from immunofluorescence and ChIP assays in the present study unequivocally prove that the KT recruitment of the Dam1 complex is not dependent upon spindle MTs in C. albicans. This suggests that there are functional differences in the Dam1 complex of S. cerevisiae and C. albicans in terms of We observed that spindle defects associated with Spc19 and Dad2 are similar to those of inner (Cse4/CENP-A and Mif2/ CENP-C; present study) and middle (Mis12/Mtw1 [42]) KT proteins in C. albicans. Mtw1, a protein that is present in the linker layer of the kinetochore, showed similar spindle defects in C. albicans (42).…”
supporting
confidence: 50%
“…This suggests that there are functional differences in the Dam1 complex of S. cerevisiae and C. albicans in terms of We observed that spindle defects associated with Spc19 and Dad2 are similar to those of inner (Cse4/CENP-A and Mif2/ CENP-C; present study) and middle (Mis12/Mtw1 [42]) KT proteins in C. albicans. Mtw1, a protein that is present in the linker layer of the kinetochore, showed similar spindle defects in C. albicans (42). Thus, the majority of the cells with short spindles and a small population with medium-long spindles is found to be a common consequence of kinetochore mutants irrespective of the layer in which they presumably are present.…”
supporting
confidence: 50%
See 1 more Smart Citation
“…In S. cerevisiae, CENP-A/Cse4 proteolysis, which is mediated by Psh1, an E3 ubiquitin ligase, restricts its localization primarily to the centromere (30,56,102). Overexpression of CENP-A/CaCse4 results in recruitment of more CENP-A/CaCse4 molecules along with other kinetochore proteins such as Mtw1 at the centromere in C. albicans (17,106). Posttranslational modifications associated with the N-terminal histone tail are related to different functional states of chromatin-like repression (silencing) or activation of transcription.…”
Section: Cenp-a: the Universal Component Of Centromeric Chromatinmentioning
confidence: 99%
“…First, there was a high propensity among the heterodiploid progeny strains to lose an entire haploid set of chromosomes from a species. Centromeres are clustered in C. albicans (2,23,30,31) and C. dubliniensis (19). The 5-FOA selection performed in this study probably enriches a population of cells where centromere clustering is somehow compromised, leading to the loss of the URA3-containing chromosome.…”
Section: Discussionmentioning
confidence: 98%